2017
DOI: 10.3390/su9101744
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Carbon Emission Reduction in China’s Public Building Sector: Retrospective Decomposition Analysis Based on STIRPAT Model in 2000–2015

Abstract: Productive building energy efficiency (BEE) work is an approved factor in the progress of sustainable urbanization in China, with the assessment of carbon emission reduction in China's public buildings (CERCPB) being an essential element of this endeavor. Nevertheless, such evaluation has been hampered by inadequate and inefficient approaches; this is the first study to utilize the Logarithmic Mean Divisia Index Type I (LMDI-I) to decompose the equation of China's public building carbon emissions (CPBCE) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Based on Equations (6)- (8), ACC 2it represents a more comprehensive accessibility measure for a city and is measured by including minimum weighted travel time and expenditure:…”
Section: Augmented Ipat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Equations (6)- (8), ACC 2it represents a more comprehensive accessibility measure for a city and is measured by including minimum weighted travel time and expenditure:…”
Section: Augmented Ipat Modelmentioning
confidence: 99%
“…Most of the carbon footprint literature [7,8] focuses on two areas. One area examines the measurement of the carbon footprint, including but not limited to overall carbon emissions [9], carbon 1 Emission reductions through substitution of other transportation modes by HSR is small, offset by output growth, and induces demand increases.…”
Section: Introductionmentioning
confidence: 99%
“…Lin Boqiang [30] explored the factors of CO 2 emissions of China's heavy industry by the Logarithmic Mean Divisia Index (LMDI) method based on the extended Kaya identity, and the result showed that energy intensity is one of the main factors, and a decline in energy intensity leads to a reduction in CO 2 emissions. Minda Ma's research indicated that the building energy efficiency declining contributed to significantly positive CO 2 emissions reduction in China's public buildings from 2001 to 2015 [31]. Rina Wu [32] drew the same conclusion for industrial sector CO 2 emissions in Inner Mongolia.…”
Section: Introductionmentioning
confidence: 82%
“…Most of the previous papers which studied the efficiency of a specific industry typically divided China into western, central, and eastern regions according to geographical location [40,41]. However, as the reform in China deepens, the gradually increasing difference in the internal efficiency between these three regions became pronounced [42].…”
Section: Division Of Research Areasmentioning
confidence: 99%